Legal Study of the Power of Proof in Civil Law (Study of Decision Number: 332/Pdt.G/2024/PN Tnn) - Simandjuntak, Reynold; Darius, Sherina; S. Landota , Sarli; P. Lombogia , Gratia (Sekolah Tinggi Ilmu Hukum Tambun Bungai Palangka Raya, 2025)
The purpose of this study is to determine the validity of the sale and purchase acquisition in evidence in decision number 332/Pdt.G/2024/PN Tnn. The method used in this research is Normative Juridical. The results of this study are that the Panel of Judges to decide the case, the Panel of Judges looks at the facts of the trial from the proof of letters, witness evidence and even other legal facts presented at the trial. Especially in deciding this case with number 332/Pdt.G/2024/PN Tnn, the panel of judges considered that the Plaintiff, who was actually burdened with proof, could not prove the truth about the arguments and claims he presented at the trial. Meanwhile, the Defendant was able to prove so accurately in denying every argument postulated by the plaintiff against the plaintiff through presenting accurate letter evidence and also witness testimony showing that the true ownership of the land that was the object of the dispute belonged to the Defendant. So the judge's consideration in looking at the flow of the trial to decide this case focuses on every evidence and fact of the trial presented by the Defendant. As well as in the burden of proof in Article 163 HIR, the plaintiff has the obligation to prove the facts they submit, while the defendant is obliged to prove the rebuttal submitted. The plaintiff is not required to prove the truth of the defendant's rebuttal, and vice versa, there is no need to prove the truth of the rebuttal.